Legality Of Shopee Paylater Payments For Shopee Platform E-Commerce Transactions In Conventional Law - Sulubara, Seri Mughni; Lubis, Hidayati Purnama; Simbolon, Nanci Yosepin; Razi, Fachrul (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
Shopee is an application engaged in online sales or e-commerce that can be accessed easily using a smartphone. Shopee paylater is a buy now pay later method provided by the Shopee platform that allows consumers to pay for a transaction at a later date, either in one payment or in installments. The research method used is qualitative descriptive research with a normative juridical approach. The legal review of shopee paylater transactions on the shopee application as internet-based technology financing for the convenience of remote electronic transactions is contained in Articles 1313, 1320, 1338 and Article 1365 of the Civil Code. To protect the interests of consumers who use shopee paylater in the shopee application, it is regulated in Articles 4, 6, 7 and Article 62 of Law Number: 8 of 1999 concerning Consumer Protection. In the Electronic and Transaction Information Law, the protection of consumer interests of shopee paylater users is regulated in Article 18 paragraph 1 of Law Number: 19 of 2016 concerning Amendments to Law Number: 11 of 2008 concerning Electronic Information and Transactions